(untitled) (Medical Forum Monthly, 2024)
Objective: Early assessment of outcome by ST segment elevation after acute myocardial infarction. Study Design: Observational study Place of study: This study was conducted at Shaheena Jamil Teaching Hospital Abbotabad & Islam Teaching Hospital Sialkot from 1st January 2012 to 30th April 2013. Material and Methods: 160 cases of acute myocardial infarction were randomly selected from the patients attending to OPD & emergency of Shaheena Jamil Teaching Hospital Abbotabad &Islam Teaching Hospital Sialkot & their peripheral Districts. Results: During the study period, 160 patients met the criteria for inclusion & were given thrombolytic therapy. Out of these, 136 (85%) patients were males & 24 (15%) patients were females. Mean age at the time of presentation was 51.0 tears. 91 (56.8) patients had acute anterior myocardial infarction, 58 (36.2%) had acute inferior myocardial infarction & 11 (6.8%) patients had miscellaneous findings. Average time lapse was 4.03 hours from onset of the chest pain to administration of streptokinase. Group ‘A’ (complete ST segment resolution) included 67 (41.8%) patients while there were 49 (30.6%) patients in group ‘B’ ( partial ST segment resolution) & 44 (27.5%)patients on group ‘C’ (no ST segment resolution) Conclusion: The ST segment was raised in all of the acute myocardial infarction cases. But ST segment was resolved in patients in which streptokinase injection was given 4 to 5 hours back.